Tackling time-reversibility in transition path sampling molecular dynamics simulations - Zahn, Dirk (Molecular Simulation, 2012)
We discuss various implementations of the transition path sampling (TPS) method to investigate rare-events in complex systems. The key focus is dedicated to the different demands posed by molecular dynamics simulations of barrier crossing events. Thus, technical issues and tricks of trade are collected from earlier simulations of reactions, conformational changes, phase transition and phase separation processes. Along this line, the improvement of time-reversible molecular dynamics algorithms and the sampling of pathways with limited time-reversibility represent the central obstacles. The latter aspect not only extends the perspectives of the conventional TPS approach, but also leads over to the transition interface sampling concept.
EAM Import::2019-03-12